2017
DOI: 10.1177/2150135116682456
|View full text |Cite
|
Sign up to set email alerts
|

Type IV Total Anomalous Pulmonary Venous Connection

Abstract: Type IV TAPVC is a rare disease with a diverse anatomic presentation. Even though a small number of the patients with obstruction underwent emergent repair, mortality remained significant. This likely represents the intrinsic lung pathology that must be considered in the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…We did not find anatomical subtypes or preoperative PVO to be risk factors as other centers have [2,9]. In particular, the mixed TAPVD subgroup has been associated with a high mortality rate [10,11]. Our institution's recent publication on the mixed TAPVD subgroup demonstrated that good results (5.6% early mortality) can be achieved after repair in patients with biventricular physiology [6].…”
Section: Commentmentioning
confidence: 60%
“…We did not find anatomical subtypes or preoperative PVO to be risk factors as other centers have [2,9]. In particular, the mixed TAPVD subgroup has been associated with a high mortality rate [10,11]. Our institution's recent publication on the mixed TAPVD subgroup demonstrated that good results (5.6% early mortality) can be achieved after repair in patients with biventricular physiology [6].…”
Section: Commentmentioning
confidence: 60%
“… 6 The wide spectrum of anatomic variation seen with this lesion could lead to failure to identify the exact anatomy of the pulmonary veins and influence the surgical outcome; hence, accurate preoperative understanding of the anatomy of the anomalous pulmonary venous connections is important. Risk factors for surgical mortality in mixed TAPVC included age < 2 months, obstructive TAPVC, pulmonary hypertensive crises, Type III mixed TAPVC, single ventricle physiology, heterotaxy syndrome, and prolonged cardiopulmonary bypass time 1,6,10 . The in‐hospital mortality in this study was 14% as compared to 5.6%–32% in other published studies (Table 3).…”
Section: Discussionmentioning
confidence: 50%
“…The in‐hospital mortality in this study was 14% as compared to 5.6%–32% in other published studies (Table 3). 1,6–12 The most common postoperative complications seen were pulmonary hypertensive crisis (28.6%), sepsis (28.6%), and seizures (21.4%). Patients who survive correction of mixed TAPVC have good mid to long‐term clinical outcomes, which was also noted in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these 103 patients, there were 11 patients with type IV TAPVC. In this report, we describe the anatomy of the pulmonary veins based on a system suggested by Chowdhury et al [14], which was validated in a large series by St. Louis et al [15]. Type IV A was characterized by a separate anomalous connection of veins from each lung: “2 + 2” pattern.…”
Section: Methodsmentioning
confidence: 99%